To find the expression equivalent to \(4(-14)\), we can evaluate the original expression and check each of the options provided.
- Calculate \(4(-14)\): \[ 4(-14) = -56 \]
Now, let's evaluate each of the options to see which one is equivalent to \(-56\):
-
56: This is not equivalent to \(-56\).
-
4(-10 + 4): \[ 4(-10 + 4) = 4(-6) = -24 \quad \text{(not equivalent)} \]
-
4 + -14: \[ 4 + -14 = 4 - 14 = -10 \quad \text{(not equivalent)} \]
-
4(-10) + 4(-4): \[ 4(-10) + 4(-4) = -40 - 16 = -56 \quad \text{(equivalent)} \]
The expression that is equivalent to \(4(-14)\) is 4(-10) + 4(-4).